Prevalence of Dental Implants in a Saudi Population - Al-Safadi, Rahaf; Al-Safadi, Riham; Al-Safadi, Reef; Al-Abduljabbar, Zahra; Al-Ghuneem, Reem; Al-Kharisi, Afnan; Al-Musa, Zhra; Al-Honazil, Maha; Al-Ajlan, Sarah (International Journal of Emerging Trends in Science and Technology, 2019)
Aim: The primary aim of this study was to detect the prevalence of dental implants in a Saudi population in the Kingdom of Saudi Arabia. The secondary objective was to describe the status of the health insurance covering dental implants in Saudi Arabia. Materials and Methods: 1831 Saudi patients aged ≥18 years with at least one missing permanent tooth and residing in the Kingdom of Saudi Arabia were randomly selected and clinically examined for implant prostheses types (single-tooth implant, implant-supported long or short span conventional fixed bridge, implant over denture). Radiographs were used too. The health insurance covering dental implants was detected. The data obtained including age, gender, systemic disease, and tobacco smoking were documented in a patient examination form then statistically analyzed using Chi-Square Test or Fisher-Freeman-Halton Test and U-Test. Results: The prevalence of dental implants among adults missing at least one tooth was 12.7%. Of those 12.7%, the majority of patients had 2-4 implants (5.4%). The majority of patients who had one implant were in the age group <40 years; patients who had >8 implants were seen in the age group ≥60. In addition, the prevalence of implant prostheses types was as the following: Single-tooth implant 75.5%, followed by implant-supported short span fixed bridge 17.1%, implant over denture 3.9%, and implant-supported long span fixed bridge 3.5%. The majority of patients treated with single-tooth implant were in the age group <40 years. There was an insignificant difference in the median number of dental implants between males and females p>0.05. Conclusion: The majority of patients were treated with single-tooth implant. Health insurance policy doesn’t cover the cost of dental implants in Saudi Arabia. Keywords: Implant, Prevalence, Prostheses/Prosthesis, Type, Patient